Acceptability and satisfaction with emma, a smartphone application dedicated to suicide ecological assessment and prevention - Morgiève, Margot; Yasri, Daniel; Genty, Catherine; Dubois, Jonathan; Leboyer, Marion; Vaiva, Guillaume; Berrouiguet, Sofian; Azé, Jérôme; Courtet, Philippe (Frontiers in Psychiatry, 2022)
Background: As mHealth may contribute to suicide prevention, we developed emma, an application using Ecological Momentary Assessment and Intervention (EMA/EMI). Objective: This study evaluated emma usage rate and acceptability during the first month, and satisfaction after one and six months of use. Methods: 99 patients at high risk of suicide used emma for 6 months. Acceptability and usage rate of the EMA and EMI modules were monitored during the first month. Satisfaction was assessed by questions in the monthly EMA (Likert scale from 0 to 10) and the Mobile App Rating Scale (MARS; score: 0 to 5) completed at months 6. After inclusion, three follow-up visits (month 1, 3 and 6) took place. Results: 75 patients completed at least one of the proposed EMAs. Completion rates were lower for the daily than weekly EMAs (60% and 82%, respectively). The daily completion rates varied according to the question position in the questionnaire (lower for the last questions, LRT= 604.26, df= 1, p-value < 0.0001). Completions rates for the daily EMA were higher in patients with suicidal ideation and/or depression than in those without. The most used EMI was the emergency call module (n=12). Many users said that they would recommend this application (mean satisfaction score of 6.92±2.78) and the MARS score at month 6 was relatively high (overall rating: 3.3± 0.87). Conclusion: Emma can target and involve patients at high risk of suicide. Given the promising users’ satisfaction level, emma could rapidly evolve into a complementary tool for suicide prevention.